2021
DOI: 10.1177/0340035221991563
|View full text |Cite
|
Sign up to set email alerts
|

The information needs and behaviour of the Egyptian elderly living in care homes: An exploratory study

Abstract: The purpose of this study is to investigate the information-seeking behaviour of the Egyptian elderly, including their information needs. A sample of 63 elderly people living in care homes was taken. It was divided into five focus groups. Of the 63 elderly people, 40 were men (63.5%) and 23 women (36.5%). Almost half (47.6%) ranged in aged from 61 to 70. About a quarter (23%) of them held a high school diploma. The highest percentage (28.6%) was labelled as average-income people. The highest percentage (60.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Hyvari et al ( 2022 ) evaluated the utility of activity sensors in identifying behavioural activity patterns of elderly home caregivers, and the results showed that behavioural activity patterns could be easily identified from motion sensor data. Many studies, such as Steinbach ( 2017 ), Guo and Willner ( 2016 ), van Tilburg and Fokkema ( 2021 ), and Mansour ( 2021 ) and their references, have investigated elderly care problems in different countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hyvari et al ( 2022 ) evaluated the utility of activity sensors in identifying behavioural activity patterns of elderly home caregivers, and the results showed that behavioural activity patterns could be easily identified from motion sensor data. Many studies, such as Steinbach ( 2017 ), Guo and Willner ( 2016 ), van Tilburg and Fokkema ( 2021 ), and Mansour ( 2021 ) and their references, have investigated elderly care problems in different countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Mansour on the information needs and behavior of elderly individuals living in care homes in Egypt offers valuable insights into the unique challenges encountered by this demographic. The aforementioned study can serve as a foundation for developing targeted interventions aimed at improving their health outcomes (13).…”
Section: Healthmentioning
confidence: 99%